Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments. (24th January 2013) - Butterfield, B. J.; Cavieres, L. A.; Callaway, R. M.; Cook, B. J.; Kikvidze, Z.; Lortie, C. J.; Michalet, R.; Pugnaire, F. I.; Schöb, C.; Xiao, S.; Zaitchek, B.; Anthelme, F.; et al.
Abstract Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.